Gini's Nuclear Family - Rolf Aaberge (Statistics Norway, Research Department, 2006)
The purpose of this paper is to justify the use of the Gini coefficient and two close relatives for summarizing the basic information of inequality in distributions of income. To this end we employ a specific transformation of the Lorenz curve, the scaled conditional mean curve, rather than the Lorenz curve as the basic formal representation of inequality in distributions of income. The scaled conditional mean curve is shown to possess several attractive properties as an alternative interpretation of the information content of the Lorenz curve and furthermore proves to yield essential information on polarization in the population. The paper also provides asymptotic distribution results for the empirical scaled conditional mean curve and the related family of empirical measures of inequality.
Keywords: D3; D63; 330; The scaled conditional mean curve; measures of inequality; the Gini coefficient; the Bonferroni coefficient; measures of social welfare; principles of transfer sensitivity; estimation; asymptotic distributions.